Pomen gozdnega roba za biotsko raznolikost, s poudarkom na plenjenju nameščenih ptičjih gnezd - Pokorny, Boštjan (Gozdarski vestnik, 1999)
A forest edge as a biotop has a notable value for the biodiversity due to the edge effect. A traditional concept considers the forest edge as an ecotone with significantly higher species diversity comparing with adjacent ecosystems. Nevertheless, the recent studies have pointed out the increasing predators` activity in a transition zone. In consequence, the forest edge could be an ecological trap for particular prey species. Negative edge effect is well known for many breeding songbirds in fragmented landscape all over the world. With the intention of finding out the influence of some ecological characteristics of landscape over birds` nesting success a field study with the artificial nests has been made. The results show that the artificial nest-predation rate is much higher in the suburban landscape compared to the forested one from which we may conclude the predators jeopardise grounding nests much more as the above-ground nests. On the contrary, the results did not show the negative edge effect. In spite of some doubts the generalistic predators should be considered as an important factor which influences speciescomposition, population density and population dynamic of ornithofauna in the fragmented landscape.
Keywords: biotopi; biotska raznovrstnost; gnezdenje; gozdni rob; plenilci; ptice